Coastal Protection of Southern Part of The Bintuni Bay From Oil Spill: An Environmental Sensitivity Index Approach - Undang Hernawan; Rahayu Kusumah Risdianto (BULLETIN OF THE MARINE GEOLOGY, 2017)
The southern part of Bintuni Bay with highly sensitive ecosystem conditions has evolved into an oil and gas industry where potential impacts on coastal and offshore environments need to be anticipated and planned comprehensively for environmental protection from oil spills. The main problem is the determination of areas that are sensitive and vulnerable to oil spills. This study is to analyze the factors and components that affect the level of environmental sensitivity and mapping Environment Sensitivity Index (ESI) to the oil spill.  The study was carried out by identifying and assessing each land units of its and use. Land use and land cover are interpreted through the use of satellite imagery with classification methods of guided satellite imagery. Field survey was also conducted in order to improve the accuracy of land use interpretation. Data analysis was performed by spatially by GIS method. The result indicated that ESI can be divided into five categories, are very sensitive (2,395.98 hectares or 2.38%), sensitive (13,133.53 hectares or 13.07%), moderately sensitive (17,902.78 hectares or 17.81%), low sensitive (52,409.14 hectares or 52.14%) and not sensitive (14,681.48 hectares or 14.61%). Although the study area is dominated by low sensitivity category, however the coastal protection from oil spill still should be prioritized.Keywords:  coastal protection, Environmental Sensitivity Index, Oil Spill, Bintuni Bay Wilayah bagian selatan Teluk Bintuni dengan kondisi ekosistem yang sangat sensitif telah berkembang menjadi industri minyak dan gas dimana potensi dampaknya terhadap lingkungan pesisir dan lepas pantai  perlu diantisipasi dan terencana secara komprehensif untuk perlindungan lingkungan dari kemungkinan tumpahan minyak. Masalah utamanya adalah penentuan daerah yang sensitif dan rentan terhadap tumpahan minyak. Penelitian ini menganalisis faktor dan komponen yang berpengaruh terhadap tingkat sensitivitas lingkungan dan pemetaan Indeks Sensitivitas Lingkungan (ISL) terhadap tumpahan minyak. Studi ini dilakukan dengan cara identifikasi dan penilaian unit lahan pada setiap penggunaan lahan. Penggunaan dan penutup lahan diinterpretasikan melalui penggunaan citra satelit dengan metode klasifikasi citra satelit terbimbing. Guna meningkatkan akurasi interpretasi penggunaan lahan juga dilaksanakan survei lapangan. Analisis data hasil penilaian unit identifikasi dilakukan secara spasial dengan metode SIG. Hasil penelitian menunjukkan bahwa ESI dapat dibagi menjadi lima kategori, yaitu sangat sensitif (2.395,98 hektar atau 2,38%), sensitif (13.133,53 hektar atau 13,07%), cukup sensitif (17.902,78 hektar atau 17,81%), sensitif rendah (52,409.14 hektar atau 52,14% dan tidak sensitif (14.681,48 hektar atau 14,61. Meskipun sebagian besar daerah daerah penelitian termasuk dalam kategori sensitif rendah, namun demikian perlindungan dari tumpahan minyak harus tetap diprioritaskan.Kata Kunci: perlindungan pantai, Indeks Sensitivits Lingkungan, tumpahan minyak, Teluk Bintuni